Control of Communicable Diseases in Human and in Animal Populations: 70th Anniversary Year of the Birth of Professor Rick Speare (2 August 1947 - 5 June 2016) - Jorg Heukelbach (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book is dedicated to the memory of Prof. Rick Speare, whose academic contribution included high-level research on zoonotic diseases and public health in general, of human and veterinarian medical interest, following the One Health approach. He dedicated much of his work to Aboriginal communities. In 2016, Rick was tragically killed in a car crash while driving to a seminar at James Cook University in Queensland, Australia. The book contains a total of 17 papers on communicable diseases in tropical environments, many of them published by Rick's former colleagues and co-researchers. Some papers contain material collected together with Rick, which for the first time is published here.